1995
DOI: 10.1126/science.7701320
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the β Chain of a T Cell Antigen Receptor

Abstract: The crystal structure of the extracellular portion of the beta chain of a murine T cell antigen receptor (TCR), determined at a resolution of 1.7 angstroms, shows structural homology to immunoglobulins. The structure of the first and second hypervariable loops suggested that, in general, they adopt more restricted sets of conformations in TCR beta chains than those found in immunoglobulins; the third hypervariable loop had certain structural characteristics in common with those of immunoglobulin heavy chain va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
157
1

Year Published

1996
1996
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(169 citation statements)
references
References 36 publications
11
157
1
Order By: Relevance
“…Our data support the assumption that the structure of the TcR resembles that of an immunoglobulin Fab fragment (15)(16)(17). Thus, the TcR would engage a surface area of '800 A2, much like the size and shape the Ha255-262-Kk complex as it is outlined in Fig.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…Our data support the assumption that the structure of the TcR resembles that of an immunoglobulin Fab fragment (15)(16)(17). Thus, the TcR would engage a surface area of '800 A2, much like the size and shape the Ha255-262-Kk complex as it is outlined in Fig.…”
supporting
confidence: 75%
“…9). The specificity of peptide-MHC interactions has been described in great detail, whereas little biochemical (10)(11)(12)(13)(14) or structural (15,16) data exist on T-cell recognition. It is generally assumed that self-MHC accounts for the majority of the T-cell target structure, whereas antigenic peptides constitute a smaller, albeit highly heterogeneous portion of this structure (8,17).…”
mentioning
confidence: 99%
“…The association of TCRs at the cell surface with the accessory molecules CD4 or CD8 also may influence the functional affinity of TCRs (3). Despite these differences, the three-dimensional structures of the two proteins are remarkably similar, with the hypervariable regions forming loops on a single face of the molecule that contacts the antigen (4)(5)(6)(7).…”
mentioning
confidence: 91%
“…Conversely, crystallographical studies on a BV8S2A1 encoded TCR ␤ chain and an AV4S2 TCR ␣ chain fragment confirmed that TCR are folded in an Ig-like manner but also indicated significant structural differences, such as different hinge structures and interstrand hydrogen bond formation (4,5). Little is still known on how TCR bind their ligand (MHCpeptide complexes).…”
Section: From the ‡Ludwig Institute For Cancer Research Lausanne Bramentioning
confidence: 99%